THE INFLUENCE OF DIGITAL CULTURE ON EMPLOYEE PERFORMANCE WITH GENERATIONAL ALIGNMENT AS A MODERATING VARIABLE - Erni, Erni; Artis, Artis; Sihite, Mislan; Novilia, Fitri; Ishak, Ishak (ITB AAS Indonesia Surakarta, 2024)
ABSTRACT This study is a quantitative study with an explanatory approach, namely an approach that makes a number of previous studies, especially the three studies mentioned above, the main spearhead for building the arguments presented in this article. The data used in this article is primary data distributed through an online questionnaire. The data contains 5 statement items from 10 questions related to Digital Culture, Employee Performance, and Generational Alignment. The data obtained were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that the Digital Culture variable can have a positive relationship direction and a significant influence on Employee Performance because the P-Value value is positive and is below the significance level of 0.05, namely 0.008. This is because a good Digital Culture if owned by an employee can make employees change difficult work into easy, increase productivity, and increase creativity. With these three things, it can also improve Employee Performance. In addition, in the next row, the second hypothesis in this article can also be proven because the P-Values also tend to be positive and are also below the significance level of 0.05, namely 0.000, which is smaller than the direct influence of 0.008. Thus, the first and second hypotheses in the article can be accepted and proven. Keywords: Digital Culture, Employee Performance, Generational Aignment